Menggali Krisis Psikospiritual dan Akhlak Manusia melalui Lensa Tasawuf - Ahmad Sholihin Sirojuddin; Kowim Sabilillah (LaKaspia, 2025)
The psychosocial crisis holds significant relevance in understanding the moral decline in modern society. This study integrates a psychospiritual approach with the Sufi framework to analyze the root causes, implications, and potential resolutions of the moral crisis. Employing a qualitative literature-based method and hermeneutical analysis of al-Ghazālī’s thought, the research explores the interrelation between psychological dynamics, spirituality, and moral formation. The findings indicate that the moral crisis stems from a disharmony among the elements of qalb (heart), ‘aql (intellect), nafs (desire), and rūḥ (spirit), exacerbated by modernization, social pressures, and the dominance of madhmūmah traits such as envy (ḥasad), arrogance (takabbur), and unchecked desire (shahwah). From a Sufi perspective, this imbalance disrupts both the vertical relationship with God (hablun min Allah) and the horizontal relationship with fellow human beings (hablun min al-nas). As a comprehensive remedy, Sufism proposes practices such as tazkiyat al-nafs (purification of the soul), muraqabah (spiritual vigilance), tawakkul (trust in God), and tafakkur (contemplation), which aim to rehabilitate the individual’s inner integrity while simultaneously fostering social cohesion.